Indications for Biceps Tenodesis in Injured Overhead Throwing Athletes Lack Consensus: A Systematic Review and Cross-Sectional Survey - Aaron D. Sciascia, Ph.D., A.T.C., P.E.S., S.M.T.C., F.A.S.S.E.T.; W. Jeffrey Grantham, M.D.; Austin V. Stone, M.D., Ph.D.; Anthony N. Baumann, D.P.T.; John D. Kelly, IV, M.D.; W. Ben Kibler, M.D. (Arthroscopy, Sports Medicine, and Rehabilitation, 2025)
Purpose: To evaluate the current clinical practice methods and the reported indications for biceps tenodesis in injured overhead throwing athletes. Methods: This study combined a survey of experienced shoulder surgeons regarding their methods of establishing indications for tenodesis surgery with a systematic review of studies that reported performing biceps tenodesis in overhead throwing athletes. Both the survey and review were designed to identify methods of making the diagnosis to delineate the preoperative and intraoperative factors used to establish biceps involvement as a major component of the clinical presentation, as well as to attempt to establish a consensus for clinical practice. Results: Eleven studies reporting on 249 overhead throwing athletes were analyzed. Elements of the history evaluation were described in 5 studies; physical examination, in 2 studies; advanced imaging, in 7 studies; and diagnostic arthroscopy, in 8 studies. One hundred nineteen responses to the survey showed a similar thought process regarding the reasoning to include biceps tenodesis, but several aspects of the process appeared to not be supported by contemporary literature. Also, there was inconsistent use of diagnostic components, with only 3 of 9 history components and 4 of 9 physical examination components being selected by more than 50% of the respondents. Conclusions: The survey revealed there was an incompletely supported reasoning process regarding indications for tenodesis and there was no consensus regarding individual components of the history or physical examination. The literature review revealed a lack of consensus regarding which elements of the diagnostic process are integral in establishing biceps involvement in injured throwing shoulders. Level of Evidence: Level IV, systematic review of Level III and IV studies and cross-sectional survey.